The associations of residential greenness with fetal growth in utero and birth weight: A birth cohort study in Beijing, China. (August 2020) - Lin, Lizi; Li, Qin; Yang, Jie; Han, Na; Chen, Gongbo; Jin, Chuyao; Xu, Xiangrong; Liu, Zheng; Liu, Jue; Luo, Shusheng; Raat, Hein; Guo, Yuming; et al.
Highlights: Evidence on residential greenness and fetal growth in utero is scarce in China. Residential greenness were beneficially associated with fetal growth in utero. The associations were stronger in women exposed to lower levels of PM2.5 . Abstract: Background: Although studies have examined the association between residential greenness and birth weight, there is no evidence regarding the association between residential greenness and fetal growth in utero. We aimed to investigate the associations of residential greenness with both fetal growth in utero and birth weight. Methods: A birth cohort (2014–2017) with 18, 665 singleton pregnancies was established in Tongzhou Maternal and Child hospital of Beijing, China. Residential greenness was matched with maternal residential address and estimated from remote satellite data using normalized difference vegetation index with 200 m and 500 m buffers (NDVI-200 and NDVI-500). Fetal parameters including estimated fetal weight (EFW), abdominal circumference (AC), head circumference (HC) and femur length (FL) were assessed by ultrasound measurements during pregnancy. Fetal parameters were standardized as gestational-age- and gender-adjusted Z-score and undergrowth was defined as Z-score < −1.88. Birth weight Z-score, low birth weight (LBW) and small for gestational age (SGA) were assessed as birth outcomes. Generalized estimating equations with the autoregressive working correlation structure and generalized linear regression were used to examine the associations of residential greenness with quantitative and categorized outcomes. Results: We found an increase Z-score of EFW [0.054, 95% confidence interval (CI): 0.020–0.087], AC (0.045, 95%CI: 0.011–0.080) and HC (0.054, 95%CI: 0.020–0.089) associated with residential greenness above NDVI-500 median compared to less than and equal to NDVI-500 median. Stratified analyses indicated that the associations might be stronger in women exposed to lower levels of particles with aerodynamic diameters ≤2.5 µm. No associations were found in the analyses of NDVI-250 with fetal growth in utero. We didn't observe significant associations of NDVI with birth weight Z-score, LBW and SGA. Conclusions: This study identified a positive association of NDVI-500 and fetal growth in utero, but we didn't observe its association with birth weight measures. Our results suggest that building sufficient green infrastructure might potentially promote early life health.